2020
DOI: 10.1055/s-0039-1690873
|View full text |Cite
|
Sign up to set email alerts
|

Activation Strategies for Earth-Abundant Metal Catalysis

Abstract: The use of earth-abundant metal-catalysed organic transformations has increased significantly in recent years. Where low-oxidation-state catalysts are required, the in situ activation of metal(II/III) salts offers an operationally simple method to access these catalysts. Here we present the development of activation strategies from the use of reducing organometallic reagents to endogenous activation. Applications in alkene and alkyne hydrofunctionalisation reactions will be used to highlight the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our investigation started by exploring the hydroboration of styrene ( 1a ) with pinacolborane (HBPin), using different kinds of commercially available nickel salts as the pre‐catalysts in the combination with substoichiometric amount of KO t Bu at 30°C (Table 1, entries 1—4). [ 8‐10,68 ] To our delight, Ni(DME)Cl 2 , Ni(cod) 2 and Ni(acac) 2 worked very well in the reaction, giving very high yields of the hydroboration product 2a (92%—97%) with excellent Markovnikov selectivity (> 99: 1, entries 1—3). These results suggested that the catalytic performance should be less relevant to the identities of the simple nickel precursors under 0.2 mol% loading (for details, see the Supporting Information (SI)).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Our investigation started by exploring the hydroboration of styrene ( 1a ) with pinacolborane (HBPin), using different kinds of commercially available nickel salts as the pre‐catalysts in the combination with substoichiometric amount of KO t Bu at 30°C (Table 1, entries 1—4). [ 8‐10,68 ] To our delight, Ni(DME)Cl 2 , Ni(cod) 2 and Ni(acac) 2 worked very well in the reaction, giving very high yields of the hydroboration product 2a (92%—97%) with excellent Markovnikov selectivity (> 99: 1, entries 1—3). These results suggested that the catalytic performance should be less relevant to the identities of the simple nickel precursors under 0.2 mol% loading (for details, see the Supporting Information (SI)).…”
Section: Resultsmentioning
confidence: 94%
“…also reported that the in situ formed boron ‘ate’ reductive species from the reaction between KO t Bu and HBPin can activate high‐ oxidation‐state cobalt complexes in 2017. [ 8‐10 ] Our group also disclosed that the alkoxide‐pinacolborane combination can activate CoI 2 . [ 68 ] Therefore, it is proposed that the in situ formed B‐H species from CsF and HBPin can activate the Ni(II) salt to metastable Ni NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation